Integrated metabolomics and intestinal microbiota analysis to reveal anti-post-weaning diarrhea mechanisms of Modified Yupingfeng Granule in Rex rabbits - Li, Dongbo; Li, Chao; Liu, Ning; Liu, Hanzhong; Yu, Zhiju; Liu, Quanjin; Shu, Gang; Lin, Juchun; Zhang, Wei; Peng, Guangneng; Zhao, Ling; Tang, Huaqiao; et al. (Frontiers in Microbiology, 2025)
IntroductionPost-weaning Diarrhea (PWD) is a kind of physiological stress diarrhea in Rex rabbits after weaning, which can lead to death in severe cases. Traditional Chinese medicine (TCM) has been widely used in animal due to its advantages of natural origin, diverse functions, safety, reliability, economy and environmental protection. Modified Yupingfeng Granule (MYPFG) is an improved Yupingfeng prescription based on the famous traditional Chinese prescription Yupingfeng (YPF), which is combined with other TCM and has obvious synergistic and additive activity in order to obtain an excellent natural medicine for PWD.MethodsIn this study, 120 weaned Rex rabbits were randomly allocated to 4 treatment groups, including control (CON), low dose (LD), medium dose (MD), high dose (HD). Rabbits were fed a control diet or a different MYPFG proportions of diet for 30 days. The study combined 16S rRNA analysis of intestinal microbiota and cecal contents metabolomics to explore the MYPFG effect on weaned Rex rabbits.ResultsMYPFG increased average daily gain, villus length to crypt depth ratio and decreased the feed to meat ratio, diarrhea frequency, mortality rate, depth of crypt (p < 0.05). The intestinal microbiota test found that MYPFG could change the abundances of Patescibacteria, Sphingobium, Ruminococcus, and Oxalobacter. Metabolomics analysis found that effect may be related to its regulation of Glycine, serine and threonine metabolism, Arginine and proline metabolism. Nicotinate and nicotinamide metabolism.DiscussionMYPFG could regulate intestinal microbiota and change the metabolic pathway of some amino acids to alleviate the PWD in Rex rabbits.